2022
DOI: 10.3389/fbioe.2021.803052
|View full text |Cite
|
Sign up to set email alerts
|

The GDF11 Promotes Nerve Regeneration After Sciatic Nerve Injury in Adult Rats by Promoting Axon Growth and Inhibiting Neuronal Apoptosis

Abstract: Introduction: Sciatic nerve injury is a common injury of the nervous system. Stem cell-based therapies, drug-based therapies and rehabilitation physiotherapy therapies are currently available, but their limited therapeutic efficacy limits their use. Here, we aimed to explore a novel lentiviral-based gene therapeutic strategy and to elaborate its mechanism.Materials and Methods: Recombinant GDF11 protein was used for the in vitro treatment of dorsal root ganglion (DRG) cells. Lentivirus was used to construct a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Due to the anti-inflammatory effects of GDF-11, it has been studied exogenously in experimental studies in processes such as fatty liver, renal injury, spinal cord injury, peripheral nerve injury, and cerebral hemorrhage, and positive results have been found regarding its protective and healing effects [40][41][42]. Previous research has demonstrated that GDF-11 can impede cell apoptosis [43], facilitate the growth of axons and synapses [44,45], and initiate neuronal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the anti-inflammatory effects of GDF-11, it has been studied exogenously in experimental studies in processes such as fatty liver, renal injury, spinal cord injury, peripheral nerve injury, and cerebral hemorrhage, and positive results have been found regarding its protective and healing effects [40][41][42]. Previous research has demonstrated that GDF-11 can impede cell apoptosis [43], facilitate the growth of axons and synapses [44,45], and initiate neuronal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In SCI, GDF11 protects the injured spinal cord by inhibiting pyroptosis and necroptosis through TFE3-mediated enhancement of autophagy ( 41 ). GDF11 also promotes nerve regeneration after sciatic nerve injury in adult rats by promoting axonal growth and inhibiting neuronal apoptosis ( 42 ). However, there is no research on the specific mechanism of GDF11 in the immune response to SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Since it was first discovered in 1999, GDF11 has been shown to be involved in normal physiological processes including erythropoiesis and embryonic development [12]. Moreover, GDF11 has been implicated in the pathophysiology of tumor growth [13][14][15], organ development [16], aging [17,18], and the nervous system [19]. GDF11 has been shown to exhibit powerful physiological functions; however, controversy exists regarding its role in cancer biology.…”
Section: Introductionmentioning
confidence: 99%